Prognostic factors in metastatic gastric carcinoma - Ben Kridis, W.; Marrekchi, G.; Mzali, R.; Daoud, J.; Khanfir, A. (PH Akademperiodyka, 2023)
Summary. Although its incidence has declined over last half-century, gastric cancer remains the second most frequent cause of cancer death in the world. The ⅔ of the patients are metastatic at diagnosis. The current study aimed to identify some determinants of survival in patients with metastatic gastric carcinoma. Materials and Methods: It was a retrospective study that involved 49 patients treated with palliative chemotherapy between January 2000 and December 2010. Factors included: age, gender, performance status, metastatic diagnosis onset (at diagnosis or later); specific metastatic sites, number of metastatic localizations, response to chemotherapy, and hemoglobin rate. Results: In univariate analysis, factors associated to a better survival were: metastasis at diagnosis, good performance status, response to chemotherapy and single metastatic site. Independent factors in multivariate analysis were: metastasis at diagnosis and single metastatic site. Conclusion: Our study confirmed many determinants on survival described in the literature.